Beyond cholesterol: the enigma of atherosclerosis revisited - Bhakdi, Sucharit; Lackner, Karl J.; Han, Shan-Rui; Torzewski, Michael; Husmann, Matthias (Thrombosis and Haemostasis, 2004)
Atherosclerosis is widely regarded as a chronic inflammatory disease that develops as a consequence of entrapment of low density lipoprotein (LDL) in the arterial intima. Native LDL lacks inflammatory properties, so the lipoprotein must undergo biochemical alterations in order to become atherogenic. Modification is commonly regarded as being dangerous because it bestows inflammatory properties onto the lipoprotein. Most current models consider oxidation to be the decisive modifying event. Here, we submit a different concept for discussion. We propose that modification of tissue-entrapped LDL is required because it enables the lipoprotein to signal to the immune system and effect its own removal. Oxidation would be too haphazard to fulfill this function. We summarize the evidence indicating that modification occurs through the action of ubiquitous hydrolytic enzymes. Enzymatically remodeled LDL binds C-reactive protein. C-reactive protein bound to remodeled LDL not only activates complement but also regulates it by inhibiting activation of the terminal complement cascade. Simultaneously, epitopes are exposed to enable the lipoprotein to be recognized and taken up by macrophages. The high density lipoprotein-dependent reverse transport pathway concludes the sequence of events that clear tissues of cholesterol in a non-inflammatory manner very similar to what has been described for the removal of apoptotic cells. It is proposed that these physiological processes occur throughout life without harm, pathology evolving only when the machinery suffers overload. Detrimental effects are then evoked primarily by the unreigned activation of complement, macrophages, and other effectors of the immune system in the lesions.
Keywords: Low density lipoprotein; cholesterol clearance; C-reactive protein; complement